IMPACT OF AGE, PHYSICAL ACTIVITY, SMOKING AND THE PRESENCE OF MYOCARDIAL INFARCTION AND THYROID DISEASES IN THE FAMILY ON THE LEVELS OF ALDEHYDIC AND KETONIC DERIVATIVES OF OXIDATIVE MODIFICATION OF PROTEINS IN THE BLOOD OF WOMEN AND MEN WITH MYOCARDIAL INFARCTS AND HYPOTHYROIDISM - Kurhaluk, Natalia; Dubik-Tota, Małgorzata; Tota, Krzysztof; Tkaczenko, Halina (Biota. Human. Technology, 2024)
The importance of thyroid hormones in maintaining homeostasis of the cardiovascular system can be inferred from clinical and experimental data showing that even subtle changes in thyroid hormone concentrations - such as those observed in subclinical hypothyroidism or hyperthyroidism and low triiodothyronine syndrome - adversely affect the cardiovascular system. Some potential mechanisms linking the two conditions are dyslipidemia, endothelial dysfunction, changes in blood pressure, and the direct effects of thyroid hormones on the myocardium. Purpose: analysis of changes in the concentration of markers of oxidative stress, e.g. oxidation of protein amino acid residues [concentration of aldehydic and ketonic derivatives of oxidatively modified proteins (OMP)] in the blood of individuals with hypothyroidism and/or myocardial infarcts, living in central Pomeranian region, depending on age, physical activity, smoking and the presence of myocardial infarcts and thyroid diseases in the family. Methodology. The level of oxidative stress markers was assessed among 225 individuals, i.e. 132 males (58.67%) and 93 females (41.33%) aged 35-71 years residing in central Pomeranian region. In the obtained blood, an assessment of levels of aldehydic and ketonic derivatives of oxidatively modified protein analyses was carried out. Scientific novelty. According to our research, the level of aldehydic derivatives of oxidative modification of proteins was significantly higher in the elderly (more than 55 years old), and the level of ketonic derivatives was higher in younger individuals (less than 55 years old) with myocardial infarction and with both myocardial infarction and hypothyroidism. This proves the intensification of oxidative stress in both presented diseases, both among the elderly and younger individuals. The highest level of aldehydic and ketonic derivatives of oxidative modification of proteins was noted among individuals with myocardial infarctions and hypothyroidism with low physical activity and among non-smokers who suffer from hypothyroidism and additionally suffered myocardial infarctions, which may indicate an increase in oxidative stress at these diseases, regardless of physical activity and smoking. The highest level of aldehydic derivatives was noted in the group of individuals with myocardial infarction and hypothyroidism with myocardial infarction in family history, which may indicate an increase in oxidative stress in both diseases, especially in this studied group. The highest level of oxidative modification of proteins was noted among individuals with myocardial infarction and hypothyroidism, individuals with thyroid diseases in their family history, as well as those with no thyroid diseases in their family history. This proves the intensification of oxidative stress in both presented diseases, regardless of the factor of thyroid diseases in the family history. Conclusions. In the course of myocardial infarction, the level of aldehydic derivatives of oxidatively modified proteins is affected by gender, while the level of ketonic derivatives of oxidatively modified proteins is affected by the presence of a myocardial infarction in the family history. The level of aldehydic derivatives of oxidative modification of proteins in individuals with hypothyroidism is influenced by low physical activity and age over 55, while the level of ketonic derivatives of oxidative modification of proteins is affected by the gender of the individuals. In the course of myocardial infarction and hypothyroidism, the level of aldehydic derivatives of protein oxidative modification is affected by age and physical activity, while the level of ketonic derivatives of protein oxidative modification is affected by the age of individuals.